Development and Validation of a Nomogram for Predicting Bronchopulmonary Dysplasia in Very-Low-Birth-Weight Infants - Zhang, Jingdi; Luo, Chenghan; Lei, Mengyuan; Shi, Zanyang; Cheng, Xinru; Wang, Lili; Shen, Min; Zhang, Yixia; Zhao, Min; Wang, Li; Zhang, Shanshan; Mao, Fengxia; et al. (Frontiers in Pediatrics, 2021)
Background Bronchopulmonary dysplasia is a common pulmonary disease in newborns and is one of the main causes of death. The aim of this study was to build a new simple-to-use nomogram to screen high-risk populations. Methods In this single-center retrospective study performed from January 2017 to December 2020, we reviewed data on very-low-birth-weight infants whose gestational ages were below 32 weeks. LASSO regression was used to select variables for the risk model. Then, we used multivariable logistic regression to build the prediction model incorporating these selected features. Discrimination was assessed by the C-index, and and calibration of the model was assessed by and calibration curve and the Hosmer-Lemeshow test. Results The LASSO regression identified gestational age, duration of ventilation and serum NT-proBNP in the first week as significant predictors of BPD. The nomogram-illustrated model showed good discrimination and calibration. The C-index was 0.853 (95% CI: 0.851-0.854) in the training set and 0.855 (95% CI: 0.77-0.94) in the validation set. The calibration curve and Hosmer-Lemeshow test results showed good calibration between the predictions of the nomogram and the actual observations. Conclusion We demonstrated a simple-to-use nomogram for predicting BPD in the early stage. It may help clinicians recognize high-risk populations.